El rol cognitivo de los φαινόμενα y su uso científico en los tratados de ciencia de Aristóteles - Berrón, Manuel (2013)
The Cognitive Role of φαινόμενα and its Scientific Use in Aristotle’s Treatises of Science”. We examine a classical discussion about the meaning of the term φαινόμενα in Aristotle. We criticize G. E. L. Owen’s interpretation who identifies its meaning with that of opinion (ἔνδοξα). Based on Aristotle’s treatises of science we propound another interpretation about this topic. Thus, we may emphasize the cognitive role that φαινόμενα have; for this, we highlight the functionthat they have while there are source of the knowledge of principles (cf. APr. I 30) as well as that they are judges of theoretical proposal with which they are in contradiction. In effect, one of the problems to be resolved is how is it possible that a contradiction exists between the principles of a science and the φαινόμενα.